2019
DOI: 10.1016/j.parkreldis.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive stimulation of the auditory feedback area for improved articulation in Parkinson's disease

Abstract: Introduction: Hypokinetic dysarthria (HD) is a common symptom of Parkinson's disease (PD) which does not respond well to PD treatments. We investigated acute effects of repetitive transcranial magnetic stimulation (rTMS) of the motor and auditory feedback area on HD in PD using acoustic analysis of speech. Methods: We used 10 Hz and 1 Hz stimulation protocols and applied rTMS over the left orofacial primary motor area, the right superior temporal gyrus (STG), and over the vertex (a control stimulation site) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 27 publications
(45 reference statements)
5
37
0
Order By: Relevance
“…It is thus suggested that impairments in auditory-vocal integration in individuals with PD may be attributed to hyperactivity in their cortical speech motor networks (Huang et al, 2016). This idea is supported by one recent study showing that improved speech articulation in individuals with PD after brain activity in the right STG was depressed by low-frequency repetitive transcranial magnetic stimulation (rTMS) (Brabenec et al, 2019).…”
Section: The Impact Of Pd On Auditory-vocal Integrationmentioning
confidence: 91%
“…It is thus suggested that impairments in auditory-vocal integration in individuals with PD may be attributed to hyperactivity in their cortical speech motor networks (Huang et al, 2016). This idea is supported by one recent study showing that improved speech articulation in individuals with PD after brain activity in the right STG was depressed by low-frequency repetitive transcranial magnetic stimulation (rTMS) (Brabenec et al, 2019).…”
Section: The Impact Of Pd On Auditory-vocal Integrationmentioning
confidence: 91%
“…The motor cortex is one of the most frequently reported stimulation targets for rTMS modulation in both healthy populations (Hartwigsen and Siebner, 2015;Cona et al, 2017) and those with brain disorders including movement disorders (Wagle Shukla et al, 2016;Brabenec et al, 2019), stroke rehabilitation (Ludemann-Podubecka et al, 2016;Lee et al, 2019), and other disorders (Siebner et al, 2003;Odorfer et al, 2019;Pei et al, 2019;Zhang et al, 2019). Some of these studies performed RS-fMRI before and after modulation and analyzed the network changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is large variation in the analytical methods applied from study to study. These included voxel-to-voxel based dynamic FC , graph theory using 24 ROIs (Lee et al, 2019), whole-brain graph theory (Pei et al, 2019), and seed-based FC (Brabenec et al, 2019). While it could be concluded that rTMS of the motor cortex modulates the motor network, such a conclusion appears too general since it is difficult to identify which specific brain areas are modulated.…”
Section: Introductionmentioning
confidence: 99%
“…Hypokinetic dysarthria (HD) is a common symptom of PD which does not respond well to PD treatments. Brabenec et al (20) investigated acute effects of repetitive transcranial magnetic stimulation (rTMS) of the motor and auditory feedback area on HD in PD using acoustic analysis of speech. The results demonstrated that low-frequency stimulation of the temporal auditory feedback area may improve articulation in PD and enhance functional connectivity between the superior temporal gyrus ST and the cortical region involved in an overt speech control.…”
Section: Biofeedback In Parkinson's Disease -Review Of the Literaturementioning
confidence: 99%